The Language Choice and the Dynamics of Language Maintenance in the Multilingual Speech Community of Bhayangkari at the Kerinci Police Department: Pilihan Bahasa dan Dinamika Pemeliharaan Bahasa dalam Komunitas Tutur Multilingual Bhayangkari Polres Kerinci - Ardi, Ririn Lovenia; Morelent, Yetty; Isnanda, Romi; Sumaryati, Sumaryati (The Future of Education Journal, 2026)
This study aims to describe language choice and the dynamics of language maintenance within a multilingual speech community in the Bhayangkari Polres Kerinci environment. A qualitative approach with a descriptive method was employed. The research data consisted of oral utterances produced by Bhayangkari members, collected through non-participant observation during both formal and informal organizational activities. The findings reveal that Indonesian is predominantly used in formal settings as the official language and a unifying medium of the organization, while local languages such as Jambi, Kerinci, Sungai Penuh, and Minangkabau are more frequently used in informal interactions as a means of language maintenance and a marker of social identity. In addition, instances of code-switching and translanguaging were identified in linguistic interactions as communicative strategies to adapt to social contexts. These findings indicate that language choice within the Bhayangkari community is dynamic and influenced by communicative situations and the speakers’ linguistic backgrounds.